Periprocedural Myocardial Injury in High‐Risk Patients With NSTEMI Pretreated With Ticagrelor for Less or More Than 6 Hours Before PCI. (3rd January 2022) - De Luca, Leonardo; Pugliese, Marco; Putini, Rita Lucia; Natale, Enrico; Piazza, Vito; Biffani, Elisabetta; Petrolati, Sandro; Musumeci, Francesco; Gabrielli, Domenico
Abstract: We assessed the impact on periprocedural myocardial injury of a ticagrelor loading dose given <6 or >6 hours before percutaneous coronary intervention (PCI) in non–ST‐elevation myocardial infarction (NSTEMI) patients at high risk. All consecutive patients pretreated with ticagrelor and undergoing PCI for a high‐risk NSTEMI have been included in the present analysis. Propensity‐score matching was performed to compare the outcomes between patients pretreated with ticagrelor for >6 hours or ≤6 hours. The primary outcome was the rate of periprocedural myocardial injury after PCI. We also recorded clinical outcomes, including major adverse cardiovascular events and major bleedings at 1 month. A total of 1216 patients with NSTEMI were deemed eligible for the study: 481 received a ticagrelor loading dose ≤6 hours (mean time, 4.3 ± 1.2 h) and 735 >6 hours (16.1 ± 8.4 hours) before PCI. Patients pretreated with ticagrelor for >6 hours presented more risk factors and comorbidities compared to others. In patients pretreated with ticagrelor for >6 hours, the rate of periprocedural myocardial injury was significantly lower compared to the other group, in the overall population (19.6% vs 37.8%; P < .0001) and in the matched cohort of 644 patients (18.9% vs 33.5%; P < .0001). The rate of major adverse cardiovascular events and major bleeding events did not differ between the two groups, in both unmatched and matched populations. The present study suggests that ticagrelor pretreatment reduces periprocedural myocardial injury in high‐risk patients with NSTEMI undergoing PCI with expected time intervals >6 hours.